2018
DOI: 10.3201/eid2407.172104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sexual Network Connectivity and Antimicrobial Drug Use on Antimicrobial Resistance inNeisseria gonorrhoeae

Abstract: Contemporary strategies to curtail the emergence of antimicrobial resistance in Neisseria gonorrhoeae include screening for and treating asymptomatic infections in high-prevalence populations in whom antimicrobial drug–resistant infections have typically emerged. We argue that antimicrobial resistance in these groups is driven by a combination of dense sexual network connectivity and antimicrobial drug exposure (for example, through screen-and-treat strategies for asymptomatic N. gonorrhoeae infection). Sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 48 publications
2
94
0
Order By: Relevance
“…Twenty-eight percent of samples had reduced susceptibility to ceftriaxone (minimum inhibitory concentration ≥0.125 mg/L) [4]. The reason for the high prevalence of commensal Neisseria with reduced antimicrobial susceptibility in these groups of patients presumably parallels the one proposed for gonorrhea: repeated cycles of reinfection/recolonization and antimicrobial exposure in individuals within a highly connected transmission-network [31].…”
Section: Discussionmentioning
confidence: 88%
“…Twenty-eight percent of samples had reduced susceptibility to ceftriaxone (minimum inhibitory concentration ≥0.125 mg/L) [4]. The reason for the high prevalence of commensal Neisseria with reduced antimicrobial susceptibility in these groups of patients presumably parallels the one proposed for gonorrhea: repeated cycles of reinfection/recolonization and antimicrobial exposure in individuals within a highly connected transmission-network [31].…”
Section: Discussionmentioning
confidence: 88%
“…There are a number of alternative explanations for why AMR may arise sooner in MSM than women. MSM may be more likely to travel abroad and acquire more resistant NG in this way 4,30 . MSM are more likely to be HIV-infected and may as a result use more antimicrobials 4 .…”
Section: Discussionmentioning
confidence: 99%
“…MSM may be more likely to travel abroad and acquire more resistant NG in this way 4,30 . MSM are more likely to be HIV-infected and may as a result use more antimicrobials 4 . Some studies have found that even after stratifying for HIV-infection status, MSM still report consuming more antimicrobials 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations